ANALISIS PENYESUAIAN DIRI MAHASISWA BARU BIMBINGAN DAN KONSELING UNIVERSITAS JAMBI PADA LINGKUNGAN BELAJAR - Rohmawati; Rahmah Ramadhoni, Sri; Yanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of self-adjustment of new students in the Guidance and Counseling Study Program, University of Jambi, Class of 2025, in the learning environment. The research employs a descriptive quantitative approach using a survey method. A total of 115 students were selected as the sample through total sampling technique, using a Likert scale questionnaire that had been tested for validity and reliability. Data were analyzed using descriptive percentage technique. The results showed that the overall level of self-adjustment was in the high category with an average of 64.49%. By indicator: overt performance 62.13% (high), adjustment to various groups 67.32% (high), personal satisfaction 63.95% (high), and social attitudes 66.01% (high). However, the ability to manage pressure only reached 39.47%, falling into the low category. These findings indicate that although most students have adapted well, some still face difficulties in managing psychological pressure during their transition to higher education. Keywords: Self-Adjustment, New Students, Guidance and Counseling